Phase Stability of LSCF/YSZ- SDC & LSCF/YSZ-SDCC Dual Composite Cathode Solid Oxide Fuel Cell - Abdul Rahman, Nurul Farhana; Ismail, Azzura; Azmi, Mohd Azham; Mahzan, Shahruddin; Abd.Rahman, Hamimah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This study presents the preparation of two types of dual composite cathode for solid oxide fuel cell (SOFC). Lanthanum Strontium Cobalt Ferrite (LSCF)/ Yttria Stabilized Zirconia (YSZ)-Samarium doped ceria (SDC) and Lanthanum Strontium Cobalt Ferrite (LSCF)/ Yttria Stabilized Zirconia (YSZ)-Samarium doped ceria carbonate (SDCC). The aims for this study are to investigate the initial stage compatibility of phase stability between the cathode and electrolyte material. Commercial powder LSCF was mixed with composite powder YSZ-SDC and YSZ-SDCC by ball milling at 550 rpm for 2 hours. Subsequently, the dual composite cathode powders were calcined at 750  for 1 hours. The behavior of LSCF/YSZ-SDC and LSCF/YSZ-SDCC dual composite cathode powders was characterized via X-ray Diffraction to determine the crystalline phase of dual composite after several process have acted on the powder. Nondestructive testing method, Fourier transform infrared spectroscopy was used to determine the existence of carbonate bond in LSCF/YSZ-SDCC powders. The finding shows that LSCF/YSZ-SDC and LSCF/YSZ-SDCC preliminary phase stability are compatible and suitable to proceed the next step.